The Effect of Education, Unemployment, and Population on Crime RatesThrough Poverty - Noor Hayati; Muzdalifah (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Crime rates in South Kalimantan Province have shown significant fluctuations, causing concern for the community and local government. High crime rates are often attributed to poverty, which encourages individuals to seek shortcuts to make ends meet. However, poverty is influenced by various factors such as education, unemployment, and population. Low education limits employment opportunities, high unemployment rates increase economic vulnerability, and high population numbers put pressure on economic and social resources. This research was conducted to: (1) determine the direct effect of education, unemployment, and population on poverty. (2) determine the direct effect of education, unemployment, population, and poverty on the crime rate. (3) determine the indirect effect of education, unemployment, and population on crime through poverty. This research uses secondary data collected from the Central Bureau of Statistics for South Kalimantan Province. The data used is Pooled data on districts/cities from 2017-2022. The approach used is a quantitative approach with the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method using SMARTPLS 4.0 software assistance. The results of the research in stage 1 show that only the Total Population variable has a significant negative direct effect on Poverty. Stage 2 shows that the variables of Education and Population have a significant positive direct effect on the Criminality Rate and Poverty has a significant negative direct effect on the Criminality Rate. Stage 3 shows that only the total population variable has a significant positive indirect effect on the crime rate through poverty.